TSHB R75G is a founder variant and prevalent cause of low or undetectable TSH in Indian Jews. Issue 1 (7th January 2022) - Shaki, David; Eskin-Schwartz, Marina; Hadar, Noam; Bosin, Emily; Carmon, Lior; Refetoff, Samuel; Hershkovitz, Eli; Birk, Ohad S; Haim, Alon
Abstract : Objective: Bi-allelic loss-of-function mutations in TSHB, encoding the beta subunit of thyroid-stimulating hormone (TSH), cause congenital hypothyroidism. Homozygosity for the TSHB p.R75G variant, previously described in South Asian individuals, does not alter TSH function but abrogates its detection by some immune detection-based platforms, leading to erroneous diagnosis of hyperthyroidism. We set out to identify and determine the carrier rate of the p.R75G variant among clinically euthyroid Bene Israel Indian Jews, to examine the possible founder origin of this variant worldwide, and to determine the phenotypic effects of its heterozygosity. Design: Molecular genetic studies of Bene Israel Jews and comparative studies with South Asian cohort. Methods: TSHB p.R75G variant tested by Sanger sequencing and restriction fragment length polymorphism (RFLP). Haplotype analysis in the vicinity of the TSHB gene performed using SNP arrays. Results: Clinically euthyroid individuals with low or undetectable TSH levels from three apparently unrelated Israeli Jewish families of Bene Israel ethnicity, originating from the Mumbai region of India, were found heterozygous or homozygous for the p.R75G TSHB variant. Extremely high carrier rate of p.R75G TSHB in Bene Israel Indian Jews ( 4%) was observed. A haplotype block of 239.7 kB in the vicinity of TSHB shared by Bene Israel and individuals of South Asian origin was detected. Conclusions: Our findings highlight the high prevalence of the R75G TSHB variant in euthyroid Bene Israel Indian Jews, demonstrate that heterozygosity of this variant can cause erroneous detection of subnormal TSH levels, and show that R75G TSHB is an ancient founder variant, delineating shared ancestry of its carriers.